Analysis of the Cycles of the Colombian Agricultural GDP 1976-2013 (2017)
The analysis of growth accounting in agricultural sector during 1976–2013 shows a strong contribution of labor factor and TFP, but a low contribution of capital. The results of the cycle estimation using different methods of time series filtering indicate the existence of three complete cycles with duration of 16 quarters (4 years). The expansions remain for 29 quarters on average (9.6 years) and contractions 4 quarters (1 year), which implies that cycles in agricultural sector are asymmetric given the long duration of expansions compared to contractions. The co-movement analysis of the agricultural GDP cycle and each of its demand components shows that aggregate variables of agricultural activity behave procyclically. The strong covariance of GDP with apparent consumption and of coffee exports and trade balance is one of the best stylized facts that have characterized the economic fluctuations in the Colombian agricultural sector during this period.